2021
DOI: 10.36902/sjesr-vol4-iss2-2021(423-430)
|View full text |Cite
|
Sign up to set email alerts
|

Visual representation of COVID-19 in Children‘s Literature: A Semiotic Analysis

Abstract: The massive spread of Coronavirus has badly affected the entire globe and lives of the people irrespective of age or gender. Children in this regard are no exemption. They are affected not only physically but also emotionally and mentally due to the virus and quarantine period. This study aims to provide a semiotic analysis of the visual representations of Covid-19 in the children’s book covers selected on a global level. These covers are new emerging literature and serve to narrate a global discourse related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…They conducted qualitative research to examine the cross-cultural narratives in such type of literature and the results showed that cyber literature developed for children carries so many cross-cultural narratives about Chinese New Year celebrations, Korean style haircuts, night markets, and English Divaphali celebrations that not only affect the children's literary fiction but also leave an impact on actual reality. Tufail, Khan, and Qureshi (2021) explored the visual representation of Covid 19 in children's literature through the lens of the semiotic approach devised by Kress and Leeuwen (2006). Meanwhile, the researcher applied the qualitative method, and the data was gathered by using the purposive sampling technique to make sure the holistic interpretation of selected covers.…”
mentioning
confidence: 99%
“…They conducted qualitative research to examine the cross-cultural narratives in such type of literature and the results showed that cyber literature developed for children carries so many cross-cultural narratives about Chinese New Year celebrations, Korean style haircuts, night markets, and English Divaphali celebrations that not only affect the children's literary fiction but also leave an impact on actual reality. Tufail, Khan, and Qureshi (2021) explored the visual representation of Covid 19 in children's literature through the lens of the semiotic approach devised by Kress and Leeuwen (2006). Meanwhile, the researcher applied the qualitative method, and the data was gathered by using the purposive sampling technique to make sure the holistic interpretation of selected covers.…”
mentioning
confidence: 99%